Popular Sovereignty in Constitutional Transition: Challenging the Validity of the Post-Reform Constitution - Setiawan, Junet Hariyo (Universitas Brawijaya, 2026)
This study examines the validity of the post-Reform amendments to the 1945 Constitution of the Republic of Indonesia from the perspective of Constitutional Law Theory. The urgency lies in a fundamental legitimacy paradox: although the amendments procedurally complied with Article 37, the People’s Consultative Assembly (MPR) derived its authority to amend the Constitution from the constitution it amended, thereby challenging the core principle of people’s sovereignty. The legal issues investigated are (1) who possesses the legal standing to challenge the validity of these amendments? (2) Which institution holds the authority to review such challenges? Prior studies by Indrayana (2007) focused on the political history of amendments, Maboudi (2020) emphasised general public participation in constitution-making, and Nugraha (2023) analysed the concept of abusive amendments. The objective is to critically evaluate the amendments’ validity with respect to procedural legitimacy, public participation, and consistency with Pancasila values. The research employs a normative juridical method, combining the concept of staatsfundamentalnorm with constitutional legitimacy theory and principles of people’s sovereignty. A critical legitimacy deficit exists: the amendment process lacked inclusive public participation and suffered from a circular legitimacy problem in which the MPR, a constitutional creation, altered its own source of authority. The amendments are procedurally legal but substantively questionable from the standpoint of people’s sovereignty. This study contributes to Constitutional Theory by highlighting the distinction between legality and legitimacy in amendment processes. It offers a comparative framework for other democracies, examining the integrity of their foundational changes, and underscores the need to institutionalise protection for constitutional identity.